2013
DOI: 10.33584/jnzg.2013.75.2926
|View full text |Cite
|
Sign up to set email alerts
|

Are diverse species mixtures better pastures for dairy farming?

Abstract: Pressure on New Zealand's largely pasture-based dairy industry has grown with a drive to increase production, expansion into new regions and demand for farmers to mitigate environmental impacts e.g., leaching of excess urinary nitrogen. A 3-year trial in the Waikato investigating the use of mixed pasture (e.g. perennial ryegrass, white clover, prairie grass, lucerne, chicory and plantain) showed similar annual dry matter (DM) production to standard pasture (perennial ryegrass and white clover) with greater yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 10 publications
3
32
0
2
Order By: Relevance
“…A two-year study in this region also showed greater DM production from diverse than standard pasture (Nobilly et al 2013). Given that increased summer DM production observed in both regions was the result of the dominance of summer tolerant chicory, plantain and/or lucerne (Nobilly et al 2013;Woodward et al 2013), greater productivity of diverse pasture in Canterbury compared with the Waikato was possibly due to an added response to irrigation. This suggests that incorporating diverse pasture in the irrigation-based Canterbury dairy systems has the potential to increase annual home-grown DM production with positive effects on milk production.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…A two-year study in this region also showed greater DM production from diverse than standard pasture (Nobilly et al 2013). Given that increased summer DM production observed in both regions was the result of the dominance of summer tolerant chicory, plantain and/or lucerne (Nobilly et al 2013;Woodward et al 2013), greater productivity of diverse pasture in Canterbury compared with the Waikato was possibly due to an added response to irrigation. This suggests that incorporating diverse pasture in the irrigation-based Canterbury dairy systems has the potential to increase annual home-grown DM production with positive effects on milk production.…”
Section: Discussionmentioning
confidence: 73%
“…Diverse pasture production was estimated using seasonal growth rates and annual herbage yields measured in diverse pastures for the two regions (Nobilly et al, 2013;Woodward et al, 2013). Feed quality for standard and diverse pastures were predicted by Molly from the feed composition generated using data from three studies (Burke, 2004;Nobilly et al, 2013;Woodward et al, 2013). The generated values for CP content and the ratio of water soluble carbohydrates (WSC):CP for the Waikato and Canterbury are shown in Figs.…”
Section: Model Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A site was established at DairyNZ's Scott Farm, Hamilton, New Zealand (37°47′ S, 175°19′ E) on a Matangi silt loam (Stiles & Singleton 1997) in autumn 2010, as part of a larger study to compare the performance of a range of pasture types on pasture and milk production (Woodward et al 2013). Site establishment began with soil testing in mid-February 2010.…”
Section: Site Establishmentmentioning
confidence: 99%